2015
DOI: 10.1182/blood.v126.23.4511.4511
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Single Dose Rasburicase 3 Mg Versus 6 Mg for the Management of Tumor Lysis Syndrome

Abstract: Introduction: Rasburicase, a recombinant form of urate oxidase, is a highly effective treatment for tumor lysis syndrome (TLS). Although the FDA-approved dose for rasburicase is 0.2 mg/kg/day for up to five days, many centers have adopted alternative dosing strategies to decrease cost, the most common being a single 6 mg dose. We hypothesized that further reducing the dose to 3 mg would result in similar efficacy and yield significant cost savings compared to the 6 mg dose strategy. Methods: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Despite this, there was no difference in SCr and corresponding percent change in SCr at 24-h between the two arms, confirming the results of Kraus et al n an African American population. 5…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite this, there was no difference in SCr and corresponding percent change in SCr at 24-h between the two arms, confirming the results of Kraus et al n an African American population. 5…”
Section: Discussionmentioning
confidence: 99%
“…5,6 A previous study conducted by Kraus et al found that, at 24 h, a single 3 mg dose was just as efficacious as a single 6 mg dose when the uric acid levels were ≤ 12 mg/dL. 5…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations